Deformable and Robust Core–Shell Protein Microcapsules Templated by Liquid–Liquid Phase‐Separated Microdroplets. Issue 19 (13th September 2021) - Xu, Yufan; Shen, Yi; Michaels, Thomas C. T.; Baumann, Kevin N.; Vigolo, Daniele; Peter, Quentin; Lu, Yuqian; Saar, Kadi L.; Vella, Dominic; Zhu, Hongjia; Li, Bing; Yang, He; et al.
Abstract: Microcapsules are a key class of microscale materials with applications in areas ranging from personal care to biomedicine, and with increasing potential to act as extracellular matrix (ECM) models of hollow organs, tissues, or biomolecular condensates. Such capsules are conventionally generated from non‐ECM materials including synthetic polymers. Here, robust microcapsules with controllable shell thickness from physically‐ and enzymatically‐crosslinked gelatin are fabricated, and a core–shell architecture is achieved by exploiting a liquid–liquid phase‐separated aqueous system in a one‐step microfluidic process. Microfluidic mechanical testing reveals that the mechanical robustness of thicker‐shell capsules could be controlled through modulation of the shell thickness. Furthermore, the microcapsules demonstrate environmentally‐responsive deformation, including buckling driven by osmosis and external mechanical forces. A sequential release of cargo species is obtained through the degradation of the capsules. Stability measurements show the capsules are stable at 37 °C for more than 2 weeks. Finally, through gel–sol transition, microgels function as precursors for the formation of all‐aqueous liquid–liquid phase‐separated systems that are two‐phase or multiphase. These smart capsules that can undergo phase transition are promising models of hollow biostructures, microscale drug carriers, and building blocks or compartments for active soft materials and robots. Abstract : Core–shell protein microgels from droplet microfluidics are both the outcomes and the precursors of all‐aqueous liquid–liquid phase separation. These microgels are responsive to environmental stimuli, and can influence drug release applications. The gel–sol transition of anisometric microgels is facilitated to characterize the liquid–liquid phase separation, two‐phase or multiphase.